The interactions of institutions on foreign market entry mode - Ang, Siah Hwee; Benischke, Mirko H.; Doh, Jonathan P. (Strategic Management Journal, 2015)
This paper examines the interaction effects of institutional differences in the cognitive, normative, and regulatory domains on cross‐border acquisition and alliance formation. Using a sample of 673 cross‐border acquisitions and alliances conducted by multinational corporations ( MNC s) from the manufacturing sector of six emerging economies ( EE s) over the period 1995–2008, we find significant mimicking (cognitive domain) of local firms' choice of ownership modes by EE firms. We also find that regulatory distance (regulatory domain) moderates the mimicking of both foreign and local firms while normative distance does not have any moderating effect. These findings contribute to our understanding of how EE MNC s mimic ownership modes in foreign market entry and how the interaction of this mimetic tendency with other institutional pillars affects these decisions . Copyright © 2014 John Wiley & Sons, Ltd.